Optimization of breastshot water wheels performance using different inflow configurations. (November 2016) - Quaranta, E.; Revelli, R.
Abstract: Breastshot water wheels are gravity hydraulic machines employed in low head sites. The scope of this work is to test the performance of a breastshot water wheel with two geometric inflow configurations: a sluice gate at different openings and two vertical overflow weirs. With the sluice gate, the maximum efficiency of the plant is 75%, constant over a wide range of flow rates, while the efficiency with the weir is increasing in the same flow rate range. Therefore, the wheel with the weir can exploit higher water volumes, and also it performs better at high power input. In practical applications, the inflow configuration can be effectively controlled to optimize the operative working conditions of breastshot water wheels, depending on the external hydraulic ones. The experimental results are also discussed in dimensionless terms, in order to support engineers in the design of similar breastshot water wheels. Highlights: Breastshot water wheels are efficient hydropower converters at low heads (<4 m). Two inflow structures for a breastshot wheel were tested, at different flow rates. The working conditions of the wheel can be optimized acting on the inflow. The inflow weir performs better than the sluice gate in extreme working conditions. Useful normalized results are achieved for the design of similar breastshot wheels.